(NkWANTOWOE IZLU^ENIE RADIOAKTIWNYH NUKLIDOW (B:s (NsPRAWO^NIK (B/s - (NgUSEW(B, (NnIKOLAJ gRIGORXEWI^s; (NdMITRIEW(B, (NpAWEL pETROWI^s ((NmOSKWA (B:s (NaTOMIZDAT(B,s, 1977)
(NbIBLIOGR(B. 730 (NNAZW(B.s
Keywords: (NaTOMNOE QDROs -- (NSPRAWO^NIKIs; (NgAMMA(B-(NLU^Is